THE INFLUENCE OF AUDIT COMMITTEE CHARACTERISTICS, EXECUTIVE COMPENSATION, AND AUDIT COMPLEXITY TOWARDS CORPORATE AUDIT FEE - Dani Angga Nugroho; Fuad Fuad (Diponegoro Journal of Accounting, 2017)
This study aimed to examine the influence of audit committee characteristics, executive compensation, and audit complexity towards corporate audit fee. The audit committee characteristics were examined by the number of its independent member, its size, meetings frequency and members’ expertise. This study used the data from company’s annual report listed on the Indonesia Stock Exchange (IDX). The populations of this study werethe companies listed on Indonesia Stock Exchange (IDX) in year 2012-2014. The samples were the non-financial companies which were selected by purposive sampling through some requirements for gaining the data in this study. There were 128 companies fulfilled criterias as the research samples. Data analysis was performed by multiple linear regression analysis method. The results of this study showed that the independent audit committee members and its meetings frequency had no significantly influence toward the corporate audit fee. Meanwhile, audit committee member’s expertise had negative influence to the corporate audit fee. Otherwise, the audit committee size, executive compensation and audit complexity had positive influences to the corporate audit fee.